Excitatory pathways from the lateral habenula enable propofol-induced sedation - Gelegen,C; Miracca,G; Ran,M; Harding,E; Ye,Z; Yu,X; Tossell,K; Houston,C; Yustos,R; Hawkins,E; Vyssotski,A; Dong,H; et al. (Current Biology, 2018)
The lateral habenula has been widely studied for its contribution in generating reward-related behaviors [1 ; 2]. We have found that this nucleus plays an unexpected role in the sedative actions of the general anesthetic propofol. The lateral habenula is a glutamatergic, excitatory hub that projects to multiple targets throughout the brain, including GABAergic and aminergic nuclei that control arousal [3; 4 ; 5]. When glutamate release from the lateral habenula in mice was genetically blocked, the ability of propofol to induce sedation was greatly diminished. In addition to this reduced sensitivity to propofol, blocking output from the lateral habenula caused natural non-rapid eye movement (NREM) sleep to become highly fragmented, especially during the rest (“lights on”) period. This fragmentation was largely reversed by the dual orexinergic antagonist almorexant. We conclude that the glutamatergic output from the lateral habenula is permissive for the sedative actions of propofol and is also necessary for the consolidation of natural sleep.